Otimização Usando Algoritmo Genéticos de Biodegradação de Querosene em Água do Mar por Candida lipolytica UCP 0988. - Cassimiro Júnior, Rivaldo (2012)
Studies have proven the ability of various microorganisms degrade petroleum and derivatives. There is a consensus that this is the main mechanism for regeneration of the environment. The natural process of biodegradation is recognized as slow and dependent on conditions such as pH, temperature, oxygen and carbon, nitrogen and phosphorus sources. In this study, the kerosene biodegradation and the biosurfactant production by Candida lipolytica UCP 0988 were investigated. Response surface methodology was used to obtain quadratic models for biomass concentration and surface tension, using data of central composite design having pH and concentrations of ammonium sulfate and potassium phosphate monobasic as independent variables and the biomass concentration and surface tension as response variables. Uniresponse and multiresponse optimization based on different hybrid approaches using response surface methodology, desirability functions and genetic algorithms have been implemented to maximize the concentration of biomass and/or minimize the surface tension of the yeast cell-free metabolic liquid. The results were validated experimentally and show that - while complying with the characteristics and limitations of each method - the different approaches can be used successfully to optimize operational conditions of media for kerosene biodegradation and biosurfactant production in seawater, leading to bioremediation processes more fast and cost-effective. . The results were validated experimentally and shown that this approach can be used successfully to optimize operating conditions and biodegradation and biosurfactant production medium in seawater, leading to faster and more cost-effective bioremediation processes.